SURGICAL METHODS IN THE COMPLEX TREATMENT OF ORTHOPEDIC PATIENTS IN PERMANENT BITE - V. І. Kutsevliak; О. V. Liubchenko; Yu. H. Danilova; V.V. Starikov (Український стоматологічний альманах, 2018)
The article presents the experimental and clinical substantiation of new solutions in orthodontics improving the efficiency and reducing the time of orthodontic treatment of patients in permanent occlusion combined method, by applying corticotomy and devices of its own design, building on mini implants, with the use of physical factors and medicines.